MENINGKATKAN PENGUASAAN SIMPLE PAST TENSE BERBENTUK IRREGULER VERBS MELALUI WORD SEARCH GAME PUZZLE SISWA KELAS XII MIPA 2 MAN 1 BANTUL - SITI DURIYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This best practice aims to improve mastery of the simple past tense in the form of irregular verbs through a word search puzzle game for class XII MIPA 2 MAN 1 Bantul students. This best practice procedure 1) The teacher conveys the learning objectives; 2) The teacher asks about the irregular verbs they know; 3) The teacher gives 30 irregular verb questions for students to work on in 15 minutes; 4) The teacher asks students to collect then gives students a puzzle game and the teacher gives an explanation about the word search puzzle game about how to do it; 5) Students in pairs work on word search puzzles; 6) The teacher discusses the correct answers from the word search puzzle game; and 7) The teacher asks the students to return to working on the irregular verb questions within 15 minutes. Based on the results of the implementation, the writer can conclude that learning using the word search game puzzle media greatly fosters positive behavior in students so that they are able to improve mastery of the simple past tense in the form of irregular verbs in class XII IPA 2 students. Simple past tense grammar material in the form of verbs irregular teaching to students through puzzles students can understand quickly, and digest well. The word search puzzle game media in a more varied form can overcome student boredom. This word search game puzzle media can be taught in other training materials. ABSTRAKBest practice ini bertujuan untuk meningkatkan penguasaan simple past tense berbentuk irreguler verbs melalui word search game puzzle siswa kelas XII MIPA 2 MAN 1 bantul. Prosedur best practice ini 1) Guru menyampaikan tujuan pembelajaran; 2) Guru menanyakan tentang irregular verb yang mereka ketahui; 3) Guru memberi soal irregular verb berjumlah 30 untuk dikerjakan siswa dalam waktu 15 menit; 4) Guru meminta siswa mengumpulkan kemudian memberikan siswa game puzzle dan guru memberi penjelasan mengenai word search game puzzle tentang cara mengerjakan; 5) Siswa secara berpasangan mengerjakan word search game puzzle; 6) Guru mendiskusikan jawaban dari word search game puzzle yang benar; dan 7) Guru meminta siswa kembali mengerjakan soal irreguler verb dalam waktu 15 menit. Berdasarkan hasil pelaksanaan, maka penulis dapat menyimpulkan sebagai berikut pembelajaran dengan menggunakan media word search game puzzle sangat menumbuhkan perilaku positif pada siswa sehingga mampu meningkatkan penguasaan simple past tense berbentuk irreguler verb pada siswa kelas XII IPA 2. Materi grammar simple past tense berbentuk irreguler verb yang diajarkan kepada siswa melalui puzzle dapat dipahami siswa dengan cepat, dan dicerna dengan baik. Media word search game puzzle dalam bentuk yang lebih variatif dapat mengatasi kebosanan siswa. Media word search game puzzle ini bisa diajarkan pada materi di mata diklat yang lain.